Pengembangan Modul Ajar Berbasis Problem Based Learning Topik Aritmatika Sosial untuk Memfasilitasi Kemampuan Pemecahan Masalah Matematis - Wiza Amelia Putri; Susda Heleni; Sakur Sakur (Aksioma, 2026)
A This research is a development research (R&D) with the aim of producing a Problem Based Learning (PBL) based teaching module on the topic of social arithmetic to facilitate mathematical problem solving skills (KPMM) of phase D students that have met the valid and practical requirements. This development research uses a 4D development model with development stages, namely defining, designing, developing and disseminating. The data collection instruments used in this study were the teaching module validation sheet and the student response questionnaire. The assessment aspect on the validation sheet assessed by 3 validators, obtained an average value of the teaching module validation results of 3.90 with a very valid category. The results of the analysis of the student response questionnaire from a small group trial of 15 respondents obtained an average value of 3.60 which was categorized as very practical.